Assessment of Predictors of Recurrent Stroke and to Analyse the Significance of Golden Hour among the Stroke Patients in a Tertiary Care Hospital - P, Sarang; R, Adwaitha; Lakshmi A, Heera; Alex, Teena Susan; MK, Soumya (Journal of Pharmacy Practice and Community Medicine)
Aim: The aim of the study is to assess the predictors of recurrent stroke and to analyze the significance of golden hour among the stroke patients in a tertiary care hospital. Materials and Methods: A prospective observational study of six month duration was conducted. All the data were documented and analyzed based on a standard protocol. Data collected were entered into Microsoft Excel. Statistical analysis was done by using Microsoft Excel. Results: A total of 100 patients were included in the study. 52% were male and 48% were female in which majority falls between 60-70 years of age. The occurrence of recurrent stroke was found to be 69% and most common co-morbid condition was hypertension (93%). Around 100 samples were included in the study, of which 15 patients (15%) arrived with in golden hour and their NIHSS score was found to be less than 14. Drugs for IVT treatment include alteplase of varying dose. Antihypertensives and antiplatelets are the drugs frequently used. The results even suggest that any efforts made, both pre- and in- hospital, are worthwhile investments in securing the best outcomes for the patient population. Conclusion: This study identified various important predictors to better identify patients suitable for thrombolysis. NIHSS and mRS scale were noted before and after the golden hour. This study strongly highlights that treatment in the Golden Hour leads to excellent outcomes in all patients, regardless of age and pre-existing co-morbidity.
Keywords: Predictors; Golden hour; Tissue plasminogen activator; National Institutes of Health Stroke Scale; Modified Rankin Scale.